OLD MANUSCRIPT COLLECTION OF PONTIANAK COMMUNITY - Pudjiastuti, Titik (UI Scholars Hub, 2023)
Similar to the Western and Eastern parts of Indonesia, the central part of the archipelago was also full of ancient kingdoms with their glorious history in the fields of culture, social, economy and politics. These include the sultanates found in five Kalimantan provinces. This writing focuses on West Kalimantan province, particularly in Pontianak city. The initial research in 2015 reveals that there are many ancient manuscripts in Pontianak, many of which are not in good condition. Such finding prompts several questions: Who are their current owners? What kind of old manuscripts found in Pontianak? How are their current conditions? This research aims to disseminate the existence and conditions of the old manuscripts found in Pontianak and to provide study materials to researchers in the fields of old manuscripts and ancient cultures. To date, there has not been any study in the Pontianak old manuscripts collection. The research method employed in this study is philology method with codicology approach. The study finds that the Pontianak old manuscripts vary in terms of characters, languages, and genres, but they are in poor conditions, requiring scrupulous care. It is also found that many owners do not appreciate the cultural heritage of their ancestors, resulting in numerous sales of manuscripts to foreign nations. In conclusion, only a handful of Pontianak old manuscripts remain, and they need to be preserved from destruction and banned from sale to other nations.